Child Trauma Experiences and Dissociative Symptoms in Women with Eating Disorders: Case-Control Study - María F. Rabito-Alcón; José I. Baile; Johan Vanderlinden (MDPI AG, 2020)
Background: many people with different diagnoses, including eating disorders, have suffered traumatic experiences in childhood. Method: a case-control study was performed. The objective of this study was to evaluate the presence of child trauma and dissociative symptoms in people with eating disorders and compare the results obtained with a control group. Participants were administered the Mini International Neuropsychiatric Interview (MINI) and the Structured Clinical Interview for Personality Disorders (SCID-II) to confirm diagnostic criteria and explore possible comorbidities. Traumatic experiences in childhood were evaluated with the Child Trauma Questionnaire in its abbreviated version (CTQ-SF), psychoform dissociation was measured with the Scale of Dissociative Experiences (DES-II) and somatoform dissociation with the Somatoform Dissociation Scale (SDQ-20). Results: women with eating disorders reported a greater severity and higher prevalence of child trauma than the control group. Significant differences were found by groups in dissociative symptoms. Conclusions: our results, in a Spanish sample, confirm the findings of previous studies.